Relationship Between Stress Levels, Nutritional Status And Menstrual Cycle Among Nursing Students - Karolin Adhisty; Rindo Ratu Adil; Firnaliza Rizona (Citra Delima Scientific journal of Citra Internasional Institute, 2026)
Menstruation is the final stage of the reproductive cycle, which is believed to be influenced by stress levels and nutritional status. These two aspects are considered the most dominant factors affecting menstrual cycle regularity in women. This study aims to analyze the relationship between stress levels and nutritional status with menstrual cycles in female students of the Nursing Study Program at Sriwijaya University. The research method used a correlational analytical design with a cross-sectional approach. A sample of 75 female students was selected using a probability sampling method with a stratified random sampling technique. Data were collected using the Kessler Psychological Disturbance Scale (K10) questionnaire and a menstrual cycle calendar sheet, and then analyzed using the Spearman rank test. The findings showed a significant positive relationship between stress levels and menstrual cycles (p = 0.0000, r = 0.402), indicating a moderate correlation where higher stress levels are associated with a greater risk of menstrual cycle irregularities. Similarly, a significant positive relationship was found between nutritional status and menstrual cycles (p = 0.012, r = 0.290). This indicates a weak correlation, suggesting that a more abnormal nutritional status increases the risk of menstrual irregularities. The conclusion of this study is that both stress levels and nutritional status are significantly correlated with menstrual cycle regularity.